The key causes of urban-rural conflict in China. (October 2015) - Yu, Ann T.W.; Wu, Yuzhe; Shen, Jiahui; Zhang, Xiaoling; Shen, Liyin; Shan, Liping
Abstract: In recent years, China has undergone an extremely rapid phase of urbanization, which has caused many acute problems between urban and rural areas. This paper identifies three categories of social, economic and environmental conflict, and investigates their significance according to the views of two different populations using a questionnaire survey and interviews. Using fuzzy set theory, the key causes of urban-rural conflict related to urbanization in China are identified. The differences in urban and rural people's perceptions of these key factors are discussed and the factors underlying these perceptions are analyzed. Highlights: To identify the key causes of urbanization related urban-rural conflict based on fuzzy set theory. To discuss urban and rural people's different perceptions for urban-rural conflict. To analyze the key causes of urban-rural conflict in China. To review property, resources and development conflicts in urban-rural conflict.